Perinuclear compartment controls calcineurin/MEF2 signaling for axonal outgrowth of hippocampal neurons - Mackiewicz, Joanna; Lisek, Malwina; Tomczak, Julia; Sakowicz, Agata; Guo, Feng; Boczek, Tomasz (Frontiers in Molecular Neuroscience, 2024)
Central to the process of axon elongation is the concept of compartmentalized signaling, which involves the A-kinase anchoring protein (AKAP)-dependent organization of signaling pathways within distinct subcellular domains. This spatial organization is also critical for translating electrical activity into biochemical events. Despite intensive research, the detailed mechanisms by which the spatial separation of signaling pathways governs axonal outgrowth and pathfinding remain unresolved. In this study, we demonstrate that mAKAPα (AKAP6), located in the perinuclear space of primary hippocampal neurons, scaffolds calcineurin, NFAT, and MEF2 transcription factors for activity-dependent axon elongation. By employing anchoring disruptors, we show that the mAKAPα/calcineurin/MEF2 signaling pathway, but not NFAT, drives the process of axonal outgrowth. Furthermore, mAKAPα-controlled axonal elongation is linked to the changes in the expression of genes involved in Ca2+/cAMP signaling. These findings reveal a novel regulatory mechanism of axon growth that could be targeted therapeutically for neuroprotection and regeneration.